2016
DOI: 10.1093/bja/aew169
|View full text |Cite
|
Sign up to set email alerts
|

Randomized evaluation of fibrinogen vs placebo in complex cardiovascular surgery (REPLACE): a double-blind phase III study of haemostatic therapy

Abstract: ClinicalTrials.gov identifier no. NCT01475669; EudraCT trial no. 2011-002685-20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 23 publications
2
115
2
4
Order By: Relevance
“…However, the data presented showed that the mean plasma fibrinogen level in both groups was > 4g/l and therefore hypofibrinogenaemia was unlikely to be contributing to bleeding. The REPLACE study; investigating FC use in cardiac surgery has recently been published (158). This study randomised patients to FC or Placebo with a 5 minute bleeding mass of >60g after separation from cardio-pulmonary bypass.…”
Section: Fibrinogen Trials In Non-traumatic Haemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…However, the data presented showed that the mean plasma fibrinogen level in both groups was > 4g/l and therefore hypofibrinogenaemia was unlikely to be contributing to bleeding. The REPLACE study; investigating FC use in cardiac surgery has recently been published (158). This study randomised patients to FC or Placebo with a 5 minute bleeding mass of >60g after separation from cardio-pulmonary bypass.…”
Section: Fibrinogen Trials In Non-traumatic Haemorrhagementioning
confidence: 99%
“…The results of FEISTY will be used to design a larger and hopefully definitive multi-centre study with the aim of addressing patient centred outcomes such as allogenic blood product transfusion requirements and mortality. By performing a pilot multi-centre study it is hoped to identify logistical issues that could impact on the design and conduct of a definitive study and potentially avoid the mistakes made in recently published FC studies (158).…”
Section: Fibrinogen Trials In Traumatic Haemorrhagementioning
confidence: 99%
“…37 These results and others from previous RCTs of fibrinogen concentrate in surgery summarized by Levy et al 38 do not highlight any thrombotic or safety concerns with fibrinogen concentrate. Further safety and adverse event data should become available for cryoprecipitate and fibrinogen concentrate with increased clinical experience and trials of fibrinogen replacement in active hemorrhage.…”
Section: Thrombotic Complicationsmentioning
confidence: 55%
“…Our original study design had to be modified because of a very slow recruitment rate due to screening failures. Despite having a simpler bleeding assessment compared with other fibrinogen studies, we encountered no diffuse bleeding after 44 patients . In addition, we changed the inclusion criteria to only patients with lower pre‐operative fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence supporting its superiority to conventional treatment using FFP and a recently published trial (FIBRES) demonstrated non‐inferiority of fibrinogen concentrate compared with Cryo usage in severe bleeding . Other studies have shown conflicting results . Results from single‐center studies with different designs (prophylactic approach or bleeding assessment) could not be confirmed by an international multicenter trial (REPLACE) .…”
Section: Introductionmentioning
confidence: 99%